SIMULASI ANTRIAN PELAYANAN NASABAH BANK MENGGUNAKAN METODE HYPEREXPONENTIAL - Pardede, Akim Manaor Hara (Journal Information System Development (ISD), 2018)
Waiting is a boring thing for some people, let alone having to queue up in long queues. In everyday life waiting in a queue is a common thing, for example the queue at the bank teller. This queue can occur due to the arrival of the increasingly enlarged and can not be offset by existing services. A long queue will keep people waiting until they get bored and even leave. This will make the bank losers due to loss of customers, on the contrary if there is no queue then the service facility (teller) many unemployed will cause losses for the bank. So needed a solution to overcome this, one of them is by simulation. Simulations are performed to simulate real existing queuing systems with properties that are easier to observe than the original system, to determine the performance of the system. In this research, Hyperexponential method is used to calculate service time with single channel to observe how system performance. Based on the results of the study, the server obtained adequate to serve is as much as 3 servers, if only 1 or 2 servers will result in the average waiting time is too long which resulted in customers will be bored waiting while while using 4 servers will result in the average waiting time zero so the server is idle